Detection of antibodies against agents of human granulocytic anaplasmosis and human monocytic ehrlichiosis serum from patients from Novosibirsk Region - V. A. Rar; N. V. Fomenko; O. V. Mel’nikova; N. Ya. Chernousova (Бюллетень сибирской медицины, 2008)
Serum samples from patients hospitalized with febrile illnesses occurring after tick bites were investigated for antibodies against agents of human granulocytic anaplasmosis (HGA) and human monocytic ehrlichiosis (HME). Ten from 205 patients were shown to contain HGA-specific antibodies, one patient — HME-specific antibodies, and one patient — both antibodies against agents of HGA and HME. Diagnosis of HGA was serologically and clinically confirmed for four patients. All patients with serologically confirmed HGA were shown to contain also antibodies against Borrelia burgdorferi sensu lato or HME-specific antibodies. Moreover, one patient was shown to be infected with tick-borne encephalitis virus. Thus, it seems reasonable to analyze patients with confirmed tick-borne encephalitis as well as with febrile illness after tick bites on the infection with HGA and HME.